Ricerche archeologiche a Sant'Andrea di Loppio (Trento, Italia) il castrum tardoantico-altomedievale - Maurina, Barbara (Archaeopress, 2016)
The island of Sant' Andrea, situated on the road that since ancient times has linked the Adige Valley with the Lake Garda, is now little more than a small hump on the edge of a vast marshy basin. Excavations reveal a multi-layered archeological site with finds ranging from the prehistoric age right through to the First World War